Poetic metaphors creativity and interpretation - Rasse, Carina (Figurative thought and language, 2022)
"Poetry pushes metaphor to the limit. Consider how many different, dynamic, and interconnected dimensions (e.g., text, rhyme, rhythm, sound, and many more) a poem has, and how they all play a role in the ways (metaphorical) meaning is constructed. There is probably no other genre that relies so much on the creator's ability to get his or her message across while, at the same time, leaving enough room for the interpreters to find out for themselves what a poem means to them, what emotions and feelings it evokes, and which experiences it conveys. This book uses interviews, questionnaires and think-aloud protocols to investigate the meanings and functions of metaphors from a poet's perspective and to explore how readers interpret and engage with this poetry. Besides the theoretical contribution to the field of metaphor studies, this monograph presents numerous practical implications for a systematic exploration of metaphors in contemporary poetry and beyond"--